2018
DOI: 10.3389/fmicb.2018.02744
|View full text |Cite
|
Sign up to set email alerts
|

Electrode Potential Dependency of Single-Cell Activity Identifies the Energetics of Slow Microbial Electron Uptake Process

Abstract: Electrochemical measurements have been widely applied to study microbial extracellular electron transport processes. However, because electrochemistry detects not only microbial electron transport but also other reactions, background signals comparable to or larger than microbial ones hamper the identification of microbial electrochemical properties. This problem is crucial especially for the detection of electron uptake processes by slow-growing microbes in low-energy subsurface sediments, as the environmenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 38 publications
(46 reference statements)
3
11
0
Order By: Relevance
“…These results demonstrated that in the presence of biosynthesized FeS, D. vulgaris obtained energy from the ITO electrode via EEU. Meanwhile, IS5 cells incubated for 3 days in the presence and absence of the −0.4 V‐poised electrode exhibited an average 15 N isotopic ratio of 1.2 % and 0.4 %, respectively, indicating that EEU via OMCs also permitted IS5 cells to acquire energy from the ITO electrode, which is consistent with a previous study …”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…These results demonstrated that in the presence of biosynthesized FeS, D. vulgaris obtained energy from the ITO electrode via EEU. Meanwhile, IS5 cells incubated for 3 days in the presence and absence of the −0.4 V‐poised electrode exhibited an average 15 N isotopic ratio of 1.2 % and 0.4 %, respectively, indicating that EEU via OMCs also permitted IS5 cells to acquire energy from the ITO electrode, which is consistent with a previous study …”
Section: Resultssupporting
confidence: 91%
“…Next, we examined whether the rate of electron uptake via FeS NPs would be sufficient for microbial energy acquisition using the previously reported native OMCs pathway in Desulfovibrio ferrophilus IS5 for comparison. Because I c generation on −0.4 V‐poised ITO electrodes by D. vulgaris cells with FeS NPs was about five times larger than that reported for IS5 cells in similar single‐chamber electrochemical reactors, EEU via biosynthesized FeS NPs may enable faster energy acquisition in cells compared to that via OMCs. However, these SRB strains may exhibit different coupling efficiencies of EEU and energy production.…”
Section: Resultsmentioning
confidence: 72%
“…However, previous work (Meyer et al, 2016) also noted a quick response to incubation conditions by the North Pond crustal fluid microbial community, proposing this as evidence that the microbes were poised to quickly take advantage of transient resources as an adaptive advantage in their resource limiting environment. This suggests that metabolic activity, rather than growth of cells, explains this current response, similar to prior experiments (Deng and Okamoto, 2018). Activity rather than growth in these experiments makes sense given that no additional resources (i.e., vitamins, minerals, and carbon) were provided in the MFC media.…”
Section: Samplesupporting
confidence: 73%
“…There is a diffuse peak between −0.9 and −0.7 V vs. Ag/AgCl. This peak covers the range at which hydrogen is abiotically generated but is in addition to the abiotic signal (Deng and Okamoto, 2018). This may indicate a capacity for using hydrogen as a source of electrons.…”
Section: Evidence Of Redox Reactions In Cathodic Eet-capable Microbiamentioning
confidence: 87%
“…In a previous study, high transcriptional levels of multiheme outer membrane cytochromes were reported in electron‐donor starved D. ferrophilus IS5 (Deng et al ., 2018). Later, it was reported that D. ferrophilus IS5 cells incubated on ITO cathodes exhibited high transcriptional levels of proteins involved in ATP synthesis and SO 4 2− reduction, but no outer membrane cytochromes (Deng and Okamoto, 2018). Since we found that all proteinaceous components for a cathodic electron uptake are present in lactate‐starved cells, we analysed the proteome of electron‐donor limited cell suspensions incubated for 100 h in the minimal medium of the electrochemical system.…”
Section: Resultsmentioning
confidence: 99%